Safe Sleep Video Intervention via Text Messaging to Low-Income Families - Rachel Y. Moon; Eve R. Colson; Fern R. Hauck; Ann L. Kellams; Margaret G. Parker; Stephen M. Kerr; Nicole L. Geller; Katherine E. Boguszewski; Scarlett L. Bellamy; Marc T. Kiviniemi; Michael J. Corwin (JAMA, 2026)
Importance Although safe sleep practices reduce the risk of sudden unexpected infant death, US rates of adherence remain low, particularly among low-income families. Objective To evaluate the effectiveness of prenatal and postnatal text-delivered video safe sleep interventions for Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) participants. Design, Setting, and Participants Unblinded 4-group randomized clinical trial of pregnant mothers recruited May 2022 through December 2024 at WIC and Federally Qualified Health Centers in 18 states, with 2 stages of randomization (at 34 weeks’ gestation and at delivery) to safe sleep or control interventions. Interventions Short educational videos promoting safe sleep (intervention) or breastfeeding (control) were delivered via text messages in the prenatal period from 34 weeks’ gestation, the postnatal period until 60 days after birth, or both. Main Outcomes and Measures Primary outcomes were maternal report of 4 infant sleep practices (usual supine sleep position, usual room sharing without bed-sharing, soft bedding nonuse, any pacifier use) at 60 or more days after birth. Secondary outcomes included exclusive supine position and room sharing without bed-sharing (collected at ≥60 days), prenatal planned exclusive supine position and room sharing without bed-sharing (reported at 36 weeks’ gestation), and time-to-initial-report of nonexclusive supine, nonexclusive room sharing without bedsharing, and soft bedding use (collected through weekly text queries). Results Of 1790 participants (86%) randomized, 1383 (77%) completed the 60+-day survey and were included in the analysis. Of these, 818 (59.1%) were aged 24 to 34 years; 323 (23.4%) were Black, 325 (23.5%) Hispanic, and 598 (43.2%) White. Participants were assigned to prenatal and postnatal intervention (n = 337), prenatal intervention alone (n = 344), postnatal intervention alone (n = 334), or control (n = 348); 12% of all participants received the intervention in Spanish. Among the primary outcomes, depending on the group, 87.6% to 92.2% of mothers reported usual supine position, 83.8% to 89.5% of mothers reported usual room sharing without bed-sharing, 75.6% to 84.5% reported no soft bedding use, and 72.5% to 76.0% reported pacifier use. There were no significant differences among groups for the primary outcomes. Among the 7 secondary outcomes, reported exclusive supine positioning at 60 days was higher among participants receiving the prenatal intervention than among controls (240/343 [70.6%] vs 212/348 [60.9%]; adjusted risk difference, 9.7% [95% CI, 3.8%-15.0%]). Conclusions and Relevance A text-delivered video intervention to promote safe sleep practices among low-income families in the prenatal and postnatal periods did not have significant effects on the primary outcomes. Trial Registration ClinicalTrials.gov Identifier: NCT04387552